UPDATING OF PNEUMATIC FEED AS FACTOR OF SEED RATE INCREASE - Valeriy V. Dolzhikov (Advanced Engineering Research)
The design and working conditions of the pneumatic disk feeds which permit to improve the cropping efficiency are proved.